Pemberdayaan Masyarakat Desa Sade Dalam Kesiapan Desa Tangguh Bencana Banjir dan Tanah Longsor - Made Sutha Yadnya; Lalu Muhamad Irfan; Abdullah Zainuddin; Bulkis Kanata; Teti Zubaidah; Rosmaliati Rosmaliati; Paniran Paniran (Universitas Mataram, 2022)
The Mandalika area has become an area of ​​global concern because it has a GP motorcycle racing circuit. Mandaika is geographically closely related to the 9 buffer villages. The village is Sade Village, which is a unified area that must be maintained due to the land being taken as backfill for the circuit construction area. Changes in land use are a threat that is already in sight due to the land becoming barren, it is necessary to provide knowledge about the dangers of disasters such as floods and landslides due to extreme weather. The obligation to provide knowledge on the dangers of flooding and landslides has been carried out with the help of funds from the DPP SPP Electrical Engineering, University of Mataram, through the Community Service program carried out by the research group on Electromagnetic Technology and Environmental Conservation for Humanity